Building market orientation in biotechnology SMEs: balancing scientific advances. (22nd August 2005) - Renko, Maija; Carsrud, Alan; Brannback, Malin; Jalkanen, Juho
This paper reports on a research project that looks at the market and science interplay in small and medium sized (SME) biotechnology firms. The construct of behavioural market orientation is our main tool for analysing science push and market pull in the biotechnology SME context. We report the findings of an action research project, in which a strategy for the pharmaceutical cluster organisation in Finland has been created. The results of this action research show the strong science and technology orientation (push) of biotechnology SMEs along with insufficient, or weak, market orientation (pull). Furthermore, our results show that the traditional components of market orientation, i.e. market intelligence generation, dissemination, and responsiveness, need to be redefined in the biotechnology context. Our findings serve as a basis for future development of a research instrument that measures market orientation in science-based firms.